2020
DOI: 10.1101/2020.02.07.938787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 3D human liver model of nonalcoholic steatohepatitis

Abstract: We developed a 3D human liver model which exhibits many features of nonalcoholic steatohepatitis and that could become a platform for medium throughput drug screening. ABSTRACTWe have developed an in vitro preclinical 3D Non-Alcoholic SteatoHepatitis (NASH) model by co-culturing four human primary liver cell types: hepatocytes, stellate, endothelial and Kupffer cells. Cells were embedded in a hydrogel of rat collagen in 96-well plate and a NASH-like environment was induced with a medium containing free fatty a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In contrast to studies presented here, the authors reported only low level of steatosis, inflammation and early fibrosis. No increased extracellular collagen fibers deposition and formation was demonstrated on histological level [51].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In contrast to studies presented here, the authors reported only low level of steatosis, inflammation and early fibrosis. No increased extracellular collagen fibers deposition and formation was demonstrated on histological level [51].…”
Section: Discussionmentioning
confidence: 84%
“…The gene expression of a range of cytokines/chemokines such as interleukin-1 (IL-1), chemokine (C-X-C motif) ligand 6 (CXCL6), C-C motif chemokine ligand 20 (CCL20), was increased by the loading of cells with FFAs and LPS (Supplementary figure 2d). Furthermore, the fibrosis biomarkers such as tissue inhibitor of metalloproteinases 1 (TIMP-1), collagens, fibronectin and elastin (Supplementary Figure 2d) were upregulated on gene expression level [2,51].…”
Section: Discussionmentioning
confidence: 99%
“…Essential factors such as spheroid size, time in culture, and culture media composition affect basal levels of xenobiotic metabolism and liver enzyme inducibility via activators of hepatic receptors such as the aryl hydrocarbon receptor (AhR), constitutive androstane receptor (CAR), and pregnane X receptor (PXR) [124]. Various co-culture techniques have also been developed for liver cell assays to recreate more tissue or disease-relevant environments for the evaluation of disease biology and toxicology [125].…”
Section: Accepted Manuscript / Final Versionmentioning
confidence: 99%